Monte Carlo investigation of prostate cancer ion therapy by using SOBP technique in the GEANT4 toolkit and MCNPX code (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Regarding the useful results concerned with an external radio-therapy in treatment of tumors, we consider in this paper a standard model of the human prostate phantom based on MIRD phantom for the Monte Carlo simulation in GEANT4 toolkit and also on MCNPX code for a prostate cancer treatment. We calculate the lateral as well as the dose profiles in the tumor region for both proton and alpha beams in a similar range, and finally having implemented the SOBP technique, we compare the results of the two beams in the corresponding codes used in this analysis.